A New Electrocardiographic Criterium to Estimate a Septal or Lateral Location of a Right-Sided Accessory Pathway - Alencar Neto, José Nunes de; Almeida Neto, Rogério Gomes de; Cirenza, Claudio; Vincenzo de Paola, Angelo Amato (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Introduction: There are algorithms to estimate the location of an accessory pathway (AP). However, in right-sided APs, they tend to present low accuracy. This paper presents a new electrocardiographic criterium to estimate the location of a right-sided AP. Materials and methods: Rest ECGs from patients with manifest pre-excitation of right-sided APs were evaluated and the SV2/RV3 ratio was calculated, considering values <1 for lateral (anterior or posterior) and ≥ 1 for septal (anterior or posterior) APs. We compared this ratio with other signs already described in literature. Results: In 175 consecutive patients, 60 met the inclusion criteria. For APs located in superior portions of tricuspid ring, the SV2/RV3 ratio <1 was 80% accurate for anteroseptal location (specificity: 75%), where His electrograms were recorded. For APs located in inferior portions of tricuspid ring A SV2/RV3 < 1 was 82,86% accurate for mid and posteroseptal location (specificity: 95.38%). Conclusion: We report a new and simple criterium that can accurately distinguish right-sided lateral and septal APs with good specificity: SV2/RV3 ratio.